Cholesterol reduction and macrophage function: role of paraoxonases. Issue 5 (October 2017) - White, C. Roger; Anantharamaiah, G.M.
Abstract : Purpose of review: Unregulated uptake of oxidized LDL by macrophages to form foam cells is the hallmark for atherosclerosis. The paraoxonase (PON) family of enzymes plays a critical role in attenuating atherosclerotic lesion formation by hydrolyzing lipid peroxides (LOOHs) and preventing the oxidation of LDL particles and by enhancing HDL-mediated cholesterol efflux. Findings in recent years suggest novel mechanisms by which PON isoforms interact with macrophages to regulate cholesterol metabolism and cellular function. Recent findings: The association of PON with HDL particles facilitates binding of the particle to macrophages and ABCA1-dependent cholesterol efflux. The hydrolysis of membrane phospholipids by PON generates lysophosphatidylcholine which is shown to regulate expression of cholesterol transport proteins. The PON family also regulates multiple aspects of macrophage function. PON attenuates inflammation and prevents induction of apoptosis via activation of a scavenger receptor class B type-1-dependent signaling mechanism. PON limits macrophage-dependent oxidant formation by preventing the activation of the membrane-associated NADPH oxidase and by stabilizing mitochondria. PON also promotes the differentiation of macrophages to an anti-inflammatory phenotype. This function appears to be independent of PON enzymatic activity and, rather, is dependent on the ability of endogenous sulfhydryls to neutralize pro-inflammatory peroxides. Summary: In recent years, the therapeutic efficacy of HDL-based therapies has been subject to dispute. Pharmacological approaches that target an increase in the expression and/or activity of PON may facilitate macrophage cholesterol metabolism and attenuate inflammatory injury.